A new species of reticulated beetle (Coleoptera: Cupedidae) from mid-Cretaceous Kachin amber, northern Myanmar. (July 2022) - Song, Zhenyu; Jarzembowski, Edmund A.; Xiao, Chuantao
Abstract: A rare archaic beetle, Mallecupes zhangi sp. nov., (Insecta: Coleoptera: Archostemata: Cupedidae) is described based on a well-preserved male specimen from mid-Cretaceous Kachin amber. It is the fourth species of the genus from the same location that can be distinguished from the other 3 congeners based on the combination of rounded temples and fingerlike produced anterior angles of the pronotum and transverse, somewhat subquadrate maculated window punctures. The function of the considerably produced anterior angles of the pronotum may be defensive.